2011
DOI: 10.1002/elan.201100149
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Mitomycin C with DNA Immobilized onto Single‐walled Carbon Nanotube/Polymer Modified Pencil Graphite Electrode

Abstract: The electrochemical investigation of the interaction between the anticancer drug mitomycin C (MC) and DNA was described using a single-walled carbon nanotube (SWCNT)/poly(vinylferrocenium) (PVF + ) modified pencil graphite electrode (PGE). The electrochemical oxidation signals of guanine were monitored before and after the interaction between MC and DNA by using differential pulse voltammetry. The effects of DNA and MC concentration and MC interaction time were examined based on the electrode response. Cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…6). The detection limit that was found in the study was comparable with the other ones reported previously [29,30,38] .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…6). The detection limit that was found in the study was comparable with the other ones reported previously [29,30,38] .…”
Section: Resultssupporting
confidence: 91%
“…The applications of electrochemical nanobiosensors are in increasing demand since they are rapid, sensitive, selective, easily prepared and low-cost devices. Much effort has been put on DNA detection for improving sensitivity, stability and reproducibility [24][25][26][27][28][29][30]. Electrochemical detection combined with nanomaterial technology achieves many of the goals mentioned above.…”
Section: Introductionmentioning
confidence: 98%
“…This decrease may be attributed that the repulsive electrostatic interactions between the OH − groups of CHIT biopolymer and anionic redox probe 33. The I c and Q c of Fe(CN) 6 3−/4− increased as 1.6 % and 3.2 % respectively after modification of PGE with 750 µg/mL CNT‐750 µg/mL CHIT mixture (Figure S1‐c Supporting Information) indicating CNT improved the electroactive surface area (Table S3 Supporting Information) and conductibility of electrode 16,11,24. After the immobilization of the 20 µg/mL fsDNA at the surface of CNT‐CHIT/PGE, I c and Q c values decreased as 69.1 % and 38.7 % respectively.…”
Section: Resultsmentioning
confidence: 99%
“…32,39,63 Firstly, the oxidation signals of the compounds were measured by using DPV technique. 32,39,63 Firstly, the oxidation signals of the compounds were measured by using DPV technique.…”
Section: Discussionmentioning
confidence: 99%